KOMPETENSI CUSTUMER SERVICE DALAM MENINGKATKAN PELAYANAN NASABAH PADA KANTOR BANK SYARIAH INDONESIA KC PADANGSIDIMPUAN - Suryadi Syabatullah; Khairina Tambunan (JOURNAL SAINS STUDENT RESEARCH, 2024)
The research aims to dig deeper into the key competencies possessed by customer service at KC Padangsidimpuan. This research uses a qualitative approach to gain an in-depth understanding of customer service competency and its role in improving customer service at the Bank Syariah Indonesia (BSI) KC Padangsidimpuan Office. By utilizing this approach, researchers can thoroughly investigate the dynamics of customer service competencies and their interactions with customers in the Islamic banking environment. Overall, in-depth customer service competency regarding sharia principles, good communication skills, and training effectiveness are key factors in creating a positive experience for customers at BSI KC Padangsidimpuan.